More successful feats by UMP undergrads at the international scene - Abdul Rahman, Ahmad (Penerbit UMP, 2015)
Six Universiti Malaysia Pahang (UMP) undergraduates did the University proud when they won three gold medals, three silver medals and one special award at the Kaohsiung International Invention and Design Expo 2015 held from December 4-6, 2015 in Kaohsiung, Taiwan.